Effects of Nitrogen and Phosphorus Inputs on Soil Bacterial Abundance, Diversity, and Community Composition in Chinese Fir Plantations - Wang, Qing; Wang, Cong; Yu, WeiWei; Turak, Ali; Chen, Diwen; Huang, Ying; Ao, Junhua; Jiang, Yong; Huang, Zhengrui (Frontiers in Microbiology, 2018)
Abstract Nutrient inputs to forest ecosystems significantly influence aboveground plant community structure and ecosystem functioning. However, our knowledge of the influence of nitrogen (N) and/or phosphorus (P) inputs on belowground microbial communities in subtropical forests is still unclear. In this study, we used quantitative PCR and Illumina Miseq sequencing of the bacterial 16S rRNA gene to investigate bacterial abundance, diversity and community composition in a Chinese fir plantation. The fertilization treatments were: no fertilizer (CK), P amendment (P), N amendment (N) and N with P amendment (NP). Additions of N decreased soil pH and bacterial 16S rRNA gene abundance by 3.95 (from 4.69 to 3.95) and 3.95×109 copies g-1 dry soil (from 9.27×109 to 3.95×109 g-1 dry soil), respectively. Bacterial richness and diversity decreased with N addition (N and NP) rather than only P input. Proteobacteria, Acidobacteria, and Actinobacteria were the predominant phyla in all treatments. Nitrogen addition increased the relative abundance of Proteobacteria and Actinobacteria by 42.0% and 10.5%, respectively, while it reduced that of Acidobacteria by 26.5%. Bacterial communities in the CK and P treatment separated from those in the N and NP treatments upon Principle Coordinates Analysis (PCoA). Phosphorus addition did not significantly affect soil bacterial communities, and no interactions between N and P inputs on microbial traits were observed. Soil pH and mineral N availability (NH4+-N and NO3--N) appeared to have a cooperative effect on bacterial abundance and community structure, with soil pH being the key influencing factor by Canonical Correspondence Analysis (CCA). These results indicate that inorganic N rather than P fertilization affected both bacterial abundance and community composition in subtropical forests. Keywords: Soil bacterial community, N and P inputs, Illumina Miseq sequencing, Chinese fir plantation, 16S rRNA gene